Design of structural elements : concrete, steelwork, masonry and timber designs to British standards and Eurocodes - Arya, Chanakya (London : Spon Press, 2009)
This concise introduction to the design of structural elements in concrete, steel, timber, masonry and composites provides up-to-date design principles and guidance in line with both British Standards and Eurocodes
Includes bibliographical references and index
Keywords: Structural design -- Standards -- United Kingdom; Structural design -- Standards -- Europe